The Effect of Outdoor Classroom Activity to the Writing Skill for Students English Department - Rauldatul Husni (Universitas Muhammadiyah Mataram, 2019)
This research is concerned with The Effect of Outdoor Classroom Activity to the Writing Skill for student’s English department Universitas of Dharmas Indonesia. The objective of this research is to find out whether there is a significant difference in teaching writing skills between the students who are taught by using outdoor classroom activity and those who are not taught by using outdoor classroom activity. The implement of outdoor classroom activity in teaching learning process especially in writing skills can be assumed students' knowledge through the solid situation such as caring students outdoor the classroom so that the students can analyze their minds through what they observe and examine precisely. Hence, this research used an experimental research that was taken at first semester students' English Department. The experimental research involved two classes of students. The sample of this research was taken randomly. Both classes were provide pre-test and post-test. Next, the students of the group were learned by proving outdoor classroom activity at the same time the control group is learned beyond outdoor classroom activity. The occur of this research, as chases: The analysis occur of the experimental class offers that the mean count of the pre-test is 45.47 and the means count of the post-test is 71.82. It offers that the experimental class can improve student writing skill in learning process.